Upaya Guru Mata Pelajaran Akhlak Dalam Menanggulangi Kenakalan Siswa Di Smp Muhammadiyah 8 Surakarta Tahun Pelajaran 2014/2015 - pujiyono, Roso, Dr. Badaruddin, M.Ag, Drs. Arif Wibowo, M.Ag (2016)
A teacher is a noble task for heavy obligations carried. A teacher of Islamic moralis an Islamic religious teacher who has a duty to shape the behavior and manners of students in accordance with the teachings of the Islamic religion. However, in the global era, teachers are also required to pay attention to the process of the growth of students. This is due to the frequent occurrence of juvenile elinquency that occurs in the school environment, family and community, which is thought to occur because of the lack of attention of parentsto their children's growing In this study the problem to be studied is the ffort made by the teacher of Islamic moral in tackling moral delinquency of students in SMP Muhammadiyah 8 Surakarta. The purpose of this study is to describe the effort and the role of the teacher in dealing the problems. The benefits from this study are reflection of the incidents that occur in the environment and enrichment of the knowledge on both teachers and students. While the practical benefits from this study is to provide feedback to all stakeholders related to education and to beconsiderations for schools in tackling juvenile delinquency. This is a field research with descriptive qualitative approach. The data collection was conducted using interview, observation, and ocumentation. While, the data analysis was conducted using inductive method. Based on the data analysis, it can be concluded that the teacher of Islamic moral has (a) personal ability; the ability where the teacher can adapt to the environment and implement to the students, (b) ability to motivate; the teacher must have commitment to motivate students and become the role model of the students, be innovator; (c) ability to be innovator having commitment of changing for the better condition, (d) to understand students' character; the teacher should understand various characters of their students in order to know the students' behavior, (e) to be wise; the teacher has to be professional on separating their problems based on the intentions, (f) ability to guide; a teacher has to be able in guiding students and be the role model of education. Keywords: teachers' of Islamic moral roles, juvenile delinquency, motivate,wise